Association between Protection Motivation and Oral Health Care Behaviors among the Elderly in Bangsaothong Sub-district, Bangsaothong District, Samutprakarn - Katanyutanon, Tuangporn; Timtong, Panon; Sukyanudit, Wariya; Khammi, Sirinapha; Lumlong, Netnapa; Wamae, Nurhafisa; Suksakha, Preedaporn (Journal of Health Sciences and Wellness, 2020)
Abstract The objectives of this cross-sectional descriptive research were to study the oral health care behaviors and to study the association between protection motivation including the perceived severity of oral diseases, perceived susceptibility of oral diseases, expectation towards results of oral health care practices and expectation towards self-efficacy in practicing oral health care and oral health care behaviors among the elderly people in Bangsaothong Sub-District, Bangsaotong District, Samutprakarn Province. The sample included 330 elderly people with least 60 years of age who were selected by using systematic random sampling. The questionnaire was used as a research tool for data collection. The study was conducted between August-December 2018. Statistics used for analyzing data were frequency, percentage, mean, standard deviation, and Spearman’s rank correlation analysis. The findings revealed that the level of oral health care behaviors of the elderly were at a high level (=3.54, SD=0.30). In each component of the oral health, the result found that the oral cleaning, dietary habit for oral health, and avoiding the behaviors which cause negative influence on oral cavity were at a high level (=3.55, 3.43, 3.84, SD=0.35, 0.37, 0.38). But the use of dental services was at a moderate level (=2.99, SD=0.87). The association between the perceived severity of oral diseases, perceived susceptibility of oral diseases, expectation towards results of oral health care practices and expectation towards self-efficacy in practicing oral health care was positively correlated with oral health care behaviors of the elderly at statistically significant of 0.05 (r=0.450, 0.468, 0.163, 0.245, p-value<0.01). The results of this research suggested that better oral health behavior of the elderly was associated with level of protection motivation.